ADAPTASI IDENTITAS KEPENDUDUKAN DIGITAL (IKD) OLEH GENERASI BABY BOOMERS DAN GENERASI X DI KABUPATEN KAMPAR - Amri Hakim; Ilham Yuri Nanda; Mhd Rafi Yahya (LPPM Universitas Abdurrab, 2024)
After the establishment of policies related to the digitization of Identity Cards in Kampar Regency, the government needs cooperation and community participation. The government needs to pay attention to the people who will accept the ID card digitization policy seen from generational differences. The Baby Boomers and X generations in the development of digitization technology can be divided into four categories based on internet usage: 1) internet illiterate, 2) master but not reliable, 3) rely blindly, and 4) rely but not master. These categories indicate the level of ability and dependence of these generations on the internet as a source of information. Based on the phenomenon of the habits of the Baby Boomers and Generation X who are not sensitive to the presence of technology, this study aims to see how digitalization for the Baby Boomers and Generation X generation in Kampar Regency in adapting and accepting the development of digitalization technology by the government. This research uses a qualitative method by involving Baby Boomers and Generation X people in Kampar Regency as informants in this research. Data collection in the study used purposive sampling. The results of this study are the adaptation of the Baby Boomers and Generation X to the adaptation of Digital Population Identity The Baby Boomers generation tends to face greater challenges in adaptation, with education level and type of employment playing a crucial role. Those who work in digitized environments or have higher education show better adaptation, while those who work in traditional sectors or have lower education experience greater difficulties. On the other hand, Generation X shows greater flexibility and willingness to adapt, driven by an awareness of the importance of technology in modern work. Although education level is also influential in Generation X, the adaptation gap is not as wide as in the Baby Boomers. Both generations recognize the potential benefits of Identity.